2009
DOI: 10.1152/ajpregu.90936.2008
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and cardiac vagal activity following resistance exercise training in young African-American and white men

Abstract: B. C-reactive protein and cardiac vagal activity following resistance exercise training in young African-American and white men. Am J Physiol Regul Integr Comp Physiol 296: R1098-R1105, 2009. First published February 4, 2009 doi:10.1152 doi:10. /ajpregu.90936.2008 Americans have a greater prevalence of hypertension and diabetes compared with white Americans, and both autonomic dysregulation and inflammation have been implicated in the etiology of these disease states. The purpose of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
2
66
0
2
Order By: Relevance
“…Furthermore, there is evidence that the mechanisms involved in cardiovascular regulation interact with each other in a nonlinear way 13 . Heffernan et al 11 also observed that 4 weeks after the end of the training, in the African-American volunteer group, the entropy values of the sample remained above those found before the start of training.…”
Section: B Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, there is evidence that the mechanisms involved in cardiovascular regulation interact with each other in a nonlinear way 13 . Heffernan et al 11 also observed that 4 weeks after the end of the training, in the African-American volunteer group, the entropy values of the sample remained above those found before the start of training.…”
Section: B Discussionmentioning
confidence: 89%
“…Of the three articles included, two used an electrocardiogram 10,11 to capture the series of R-R intervals and one used the Suunto T6 Wristop heart rate monitor. 12 …”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] We hypothesised that a 20-week training programme would have improved blood pressure variables when compared with week 1, instead we found that SBP and MAP remained unchanged, and only the decrease in DBP was statistically significant (Table 4). Week 1 measurements of resting blood pressure showed that only one participant had an elevated SBP (152 mmHg).…”
Section: Discussionmentioning
confidence: 68%
“…[1,2] Black Africans have stiffer large central arteries, impaired dilation of small peripheral arteries and a greater prevalence of hypertension, diabetes and cardiovascular disease. [2][3][4] It is well established that a number of cardiovascular indices, such as arterial stiffness, blood pressure and autonomic regulation, are differentially affected by ageing. [5] The influence of western lifestyle (sedentary behaviour and increased consumption of high-energy processed foods) and rural urbanisation in sub-Saharan Africa has seen a shift in the underlying population distribution of risk factors for cardiovascular disease.…”
mentioning
confidence: 99%